Pendampingan Pelatihan Scoorsheet dan Wasit Bola Voli Pada Mahasiswa Boven Digoel - Hendra Jondry Hiskya; Beatus Tambaip; Jori Lahinda; Emanuel Lewar; Damaris Marlisa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Papua has slightly different characteristics from other regions. Abundant natural resources are not comparable to the state of human resources. The purpose of this service is to facilitate students to be able to understand filling out the scoresheet and refereeing training. This can be seen in one of the sports fields. What is seen here is based on the results of sports achievements. Methods carried out At this preparatory stage, make preparations by preparing all the needs regarding the material. In this activity students are assisted according to their assignments. The training stages are used to train volleyball scoresheets. Based on this activity, students who are participants in service activities can continue to teach and socialize to friends who do not know and students are very enthusiastic about participating in activities well. The next hope is that there can be cooperation between the Partners and the campus as an extension of the implementation of academic knowledge